Distinct Tlr4-expressing cell compartments control neutrophilic and eosinophilic airway inflammation - McAlees, Jaclyn W. (Mucosal Immunol, 2014)
Allergic asthma is a chronic, inflammatory lung disease. Some forms of allergic asthma are characterized by Th2-driven eosinophilia while others are distinguished by Th17-driven neutrophilia. Stimulation of Toll-like receptor 4 (TLR4) on hematopoietic and airway epithelial cells (AECs) contributes to the inflammatory response to lipopolysaccharide (LPS) and allergens, but the specific contribution of TLR4 in these cell compartments to airway inflammatory responses remains poorly understood. We used novel, conditionally mutant Tlr4(fl/fl) mice to define the relative contributions of AEC and hematopoietic cell Tlr4 expression to LPS- and allergen-induced airway inflammation. We found that Tlr4 expression by hematopoietic cells is critical for neutrophilic airway inflammation following LPS exposure and for Th17-driven neutrophilic responses to the house dust mite (HDM) lysates and ovalbumin (OVA). Conversely, Tlr4 expression by AECs was found to be important for robust eosinophilic airway inflammation following sensitization and challenge with these same allergens. Thus, Tlr4 expression by hematopoietic and airway epithelial cells controls distinct arms of the immune response to inhaled allergens.